COMPENSATION FOR GOVERNMENTAL LAWLESSNESS (International Journal of Food and Nutritional Sciences, 2023)
The law of lability of government for the tortious acts of its employees acting in the course of their employment as such is found in Article 300 of the Indian Constitution.1 But the framers of this Article, perhaps, were uncertain about the future and thus deliberately avoided any clear-cut rule for the liability in tort by governmental actions.They left the courts to search themselves from the monarchial treasure trove some fanciful immunity, and thereby left the litigants to gamble in each case without any specific legal principle.2 The Government has also usually put forth the defence of sovereign immunity whenever compensation claims for injuries caused to Indian citizens out of the routine activities of governmental agencies have been pressed, as if the Directive Principles and the Preamble to the Constitution did not exist. One of the outdated theories, going back to the days of the East India Company,3 was knocked down by the Supreme Court in Rudal Sah v State of Bihar 4 The Supreme Court in this case has used the writ jurisdiction under Article 32 to award compensation to victims of the government's wrongful acts and awarded Rudal Sah Rs. 35,000 as compensation for his detention in Muzaffarpur jail for 14 years despite his acquittal. The Supreme Court has thus broken fresh ground by opening up new vistas for citizens to hope for compensation when they become victims of State-inflicted wrongs.